(untitled) (Journal of Innovation in Academia, 2025)
The examination of the adoption of digital payment methods in Nepal is of paramount importance as it sheds light on behaviors related to financial technology that can shape the future of the country’s financial system and contribute to its economic development. This study aims to explore the factors influencing the adoption intention of digital payment systems in Pokhara Metropolitan City, Nepal. The study population consists of the youth of Pokhara, with 400 respondents selected using a purposive sampling technique. The exploratory factor analysis extracted six factors, which include effort expectancy, performance expectancy, security and privacy, social influence, facilitating conditions, and adoption intention. The structural equation modeling reveals that security and privacy, performance expectancy, and facilitating conditions have a significant positive impact on the adoption intention, whereas effort expectancy and social influence do not significantly affect the adoption intention of digital payments.